Biskuit mocaf–garut tinggi zat besi meningkatkan kadar Fe darah dan kadar hemoglobin pada tikus Sprague Dawley - Sari, Hesti Permata; Agustia, Friska Citra; Subardjo, Yovita Puri; Ramadhan, Gumintang Ratna (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2018)
Background: Biskuit are the most popular snack. Agustia et al (2016) have found biscuit made from mocaf-arrowroot substituted chicken’s liver and red spinach that has hight level of iron.Objectives: The aim of this research was to determine the bioassay value of this biscuit. Methods: The experiment was a trial of anemia recovery by providing 32 wistar rats with no iron-containing feeding for 7 days then continued for 14 days were given into 4 treatment groups, ½ serving biscuit (0.2 gram), 1 serving (0.8 gram) and 2 servings (0.4 grams) Statistical analysis was performed by using ANOVA dan LSD. Results: The result showed that there are differences between groups  (p:0.00) and we found that the highest increase of Blood Fe and haemoglobin was in the group with 2 servings of biskuist (6.65 ± 0.49 µg/dl ; 3.62 ± 0.06 gr/dl).Conclusion: Biscuit made from mocaf-arrowroot substituted liver and spinach can increase Blood Fe and haemoglobin in anemia rat.